PERFORMA KOMODITAS MINYAK SAWIT INDONESIA DI TATARAN GLOBAL: MAMPUKAH KITA MENJADI PEMAIN KUNCI? - Zukha Latifah; Kadir Kadir (University of Jember, 2021)
Palm oil is important Indonesia's export commodities. Amidst the strong position, Indonesia's palm oil exports face many challenges. This study aims to identify the performance of Indonesian palm oil compared to competing countries, the competitiveness, the market position, and the potential development of the commodity in several major trading partners. The results of Revealed Comparative Advantage and Trade Specialization Index calculations show that Indonesia's comparative competitiveness is the highest among other major exporters or producers, and Indonesia's exports are at the maturity stage. Regarding Market Position Matrix and X-Model of Potential Export Products Clusterization, the Indonesian palm oil markets in India, China, and the USA are rising stars and optimistic about developing. Meanwhile, in Pakistan and Malaysia, Indonesia experienced a lost opportunity, and the Spanish market was in a falling position but still had the potential to be improved due to the high competitiveness of the product. On the other hand, in Netherlands and Italy, it experienced a retreat, allegedly due to negative sentiment towards palm oil as the cause of various environmental destruction.